(untitled) (International Journal of Economics Management and Social Science, 2026)
This article examines George Herbert Mead’s symbolic interactionism theory, focusing on self construction and identity formation through social interaction. Mead’s framework, articulated primarily in Mind, Self, and Society (1934), posits that the self emerges not as an innate essence but through social processes involving symbolic communication and role-taking. Drawing on contemporary research in identity studies and social psychology, this study analyzes how Mead’s concepts of the "I" and "Me," the generalized other, and significant symbols remain relevant for understanding identity formation in modern contexts characterized by digital communication, globalization, and increasing social diversity. The analysis demonstrates that symbolic interactionism provides valuable insights into contemporary phenomena including online identity construction, multicultural identity negotiation, and the role of social media in self-presentation. Findings reveal that while Mead’s theory was developed in early twentieth-century American society, its core insights about the social nature of selfhood apply to twenty-first century contexts, though requiring adaptation to account for digital interaction, mediated communication, and globalized social networks. This article contributes to sociological theory by demonstrating symbolic interactionism’s continued relevance while identifying areas where the framework requires extension to address contemporary realities. Keywords: Symbolic interactionism, George Herbert Mead, self construction, identity formation, social interaction, role-taking, generalized other, significant symbols